Proceedings of the 2nd International Conference on Higher Education Advances 2016
DOI: 10.4995/head16.2016.2431
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying Impromptu Speech for ESL/EFL Students

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…This characteristic comes from Girardelli et al's ( 2016 ) work. The debater decides which arguments to use, which to attack, and whether to make use of one particular linguistic register or another.…”
Section: Concept Reviewmentioning
confidence: 89%
See 3 more Smart Citations
“…This characteristic comes from Girardelli et al's ( 2016 ) work. The debater decides which arguments to use, which to attack, and whether to make use of one particular linguistic register or another.…”
Section: Concept Reviewmentioning
confidence: 89%
“…According to Girardelli et al ( 2016 ) storytelling is a characteristic of games. Debate does not fulfill the criteria of having a narrative that structures the game, since, unlike a video game or roleplay game, there is no narrative to act as a through-line.…”
Section: Concept Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gamification is a promising trend and more engaging than non-game context (Nahmod, 2017). Empirical studies showed positive gamification effects on EFL oral proficiency (Girardelli, Barroero & Gu, 2016); grammar (Rahayu & Purnawarman, 2019;Zarzycka-Piskorz, 2016). ; learners' intrinsic and extrinsic motivation and interest to learn English (Wu & Huang, 2017;Sun & Hsieh 2018;Medina & Hurtado, 2017).…”
Section: Gamification In Efl and Previous Studies On Vocabulary Learningmentioning
confidence: 99%